"Poetic License": Constructing Literary Performing Arts Curriculum Within a High-Stakes Educational Environment - Adorador-Knudsen, Nayeli Ariel (My University, 2014)
"Poetic License" Constructing Literary Performing Arts Curriculum Within a High-Stakes Educational Environment Nayeli Adorador-Knudsen Chair of the Supervisory Committee: Professor, Dr. Michael S. Knapp Educational Leadership & Policy Studies Literary Performing Arts (LPA) is an artistic writing strategy, based within traditions of hip-hop and urban youth culture, that infuses writing with performance technique as a way to critique and resist current societal structures while also developing a students' personal dialogue with their own experiences. Three high school sites within the same urban district were examined to see how LPA curriculum functioned within a high-stakes environment at both school and classroom levels. Qualitative findings indicated that LPA curriculum and its dissemination within each learning space was in fact influenced by this high-stakes environment through external school factors such as: curricular school-wide models, active support from school administration, teacher values, and student population.
Thesis (Master's)--University of Washington, 2013
Keywords: High Stakes; Language Arts; Performing Arts; Poetry; School Accountability; Spoken Word; Performing arts education; Language arts; Education; education - seattle